Quality of life and treatment adherence in hypertensive patients: systematic review with meta-analysis - Ana Célia Caetano de Souza; José Wicto Pereira Borges; Thereza Maria Magalhães Moreira
ABSTRACT OBJECTIVE To verify the effects of antihypertensive treatment (pharmacological and non-pharmacological) on the health-related quality of life of individuals with hypertension. METHODS We conducted a systematic review with meta-analysis using the following databases: IBECS, LILACS, SciELO, Medline, Cochrane, Science Direct, Scopus and the Brazilian Capes Theses and Dissertations Database. The statistical analysis was performed using Review Manager, version 5.2. The average difference was used for the summarization of meta-analytic effect by the fixed-effect model. Twenty studies were included. RESULTS The summarization of the effect showed an average increase of 2.45 points (95%CI 1.02-3.87; p < 0.0008) in the quality of life of individuals adhering to non-pharmacological treatment for arterial hypertension. Adherence to pharmacological treatment indicated an average increase of 9.24 points (95%CI 8.16-10.33; p < 0.00001) in the quality of life of individuals with arterial hypertension. CONCLUSIONS Non-pharmacological treatment improves the overall quality of life and physical domain of people with arterial hypertension. Adherence to pharmacological treatment has a positive impact on the mental and physical domains of patients, as it did on the overall quality of life score.